2007
DOI: 10.1080/10641960701615683
|View full text |Cite
|
Sign up to set email alerts
|

Possible Influence of Spiritual and Religious Beliefs on Hypertension

Abstract: Religious and spiritual beliefs are beneficial in stroke patients as coping strategies. This work has investigated the feeling of people about it by proposing to 174 volunteers aged 54.0 +/- 16.9 years the Royal Free Interview (RFI). Interviewed subjects considered the beliefs beneficial for health independently of their form. Ascertaining the pre-morbid understanding of life in subjects at risk of hypertension may be useful to verify self-confidence and coping possibilities against anger, fear, and stress, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…[ 17 ] Likewise, some studies have indicated that patients with hypertension use religion and spirituality to control and adapt to their disease. [ 18 ] What is interesting here is that the relationship between religion and health in elderly people and patients with hypertension has not always been reported positive. Some studies implied that religious beliefs had no effects on patients’ health, which is due to increased anger, feeling of guilt, lack of self-confidence and increased distress, and psychological and spiritual distress.…”
Section: Introductionmentioning
confidence: 93%
“…[ 17 ] Likewise, some studies have indicated that patients with hypertension use religion and spirituality to control and adapt to their disease. [ 18 ] What is interesting here is that the relationship between religion and health in elderly people and patients with hypertension has not always been reported positive. Some studies implied that religious beliefs had no effects on patients’ health, which is due to increased anger, feeling of guilt, lack of self-confidence and increased distress, and psychological and spiritual distress.…”
Section: Introductionmentioning
confidence: 93%
“…3 Empirical evidence demonstrates the relationship between spirituality and self-management of hypertension, 4 but few studies have examined the impact of spirituality on diabetes self-management. 5 Thus, little is known about how spiritual beliefs and practices and social support affect self-care of diabetes in African American adults.…”
mentioning
confidence: 99%
“…Spiritual and religious beliefs and activities can aid in coping with a chronic illness by providing support, confidence, and hope, or they can interfere with successful coping, as people may neglect self-care activities by relying on prayer or meditation to manage their illness. 3 Empirical evidence demonstrates the relationship between spirituality and self-management of hypertension, 4 but few studies have examined the impact of spirituality on diabetes self-management. 5 Thus, little is known about how spiritual beliefs and practices and social support affect self-care of diabetes in African American adults.…”
mentioning
confidence: 99%
“…Some researchers have attempted to explain the link between spirituality and HTN. In an Italian study, Giaquinto and Spiridigliozzi (2007) found that spirituality functioned to increase coping and decrease vulnerability. Lewis and Ogedegbe's (2008) Model of Spirituality and Medication Adherence for African Americans diagnosed with HTN proposed that relationships with God, others, and self lead to increased social support and self‐efficacy that leads to resources to overcome barriers and finally medication adherence.…”
Section: Discussionmentioning
confidence: 99%